Somebody's daughter : the hidden story of America's prostituted children and the battle to save them - Sher, Julian, 1953- (Chicago, Ill. : Chicago Review Press, 2011)
Exposes the problem of child prostitution in the United States, sharing stories of American girls caught in the sex trafficking trade, and introduces police officers and activists who are trying to protect and rescue these young victims.
Innocence lost -- The girl from Jersey -- High-risk victims -- Maria's dilemma -- The wealth of knowledge -- Confronting the pimps -- Taking on pimp culture -- "He was untouchable" -- Takedown -- "She's not your ho anymore" -- "Like attacking the mafia" -- In the dead of the night -- "Judge people by courage" -- "Girls are not for sale" -- Courtroom 18 -- No safe haven -- Unequal laws -- Finding their own voice -- Making the invisible visible -- Epilogue : "Caught in between two worlds".
Includes bibliographical references and index.
Keywords: Child prostitutes -- United States; Child prostitutes -- United States -- Prevention